Management Distal Radius and Distal Ulnar Fractures with Fragment Specific Plate - Geissler, William B. (Journal of Wrist Surgery, 2013)
This article describes the use of a new generation low profile dorsal rim plate for management of distal radius fractures from the dorsal approach. This plate was designed to maximize stability while minimizing complications from the extensor tendons. A volar ulnar plate designed to specifically stabilize fractures of the ulnar head and neck is also described.
Keywords: dorsal plate; distal radiu; distal ulnar fracture